Measuring Norms and Normative Contestation: The Case of International Criminal Law. Issue 1 (20th February 2019) - Simmons, Beth A; Jo, Hyeran
Abstract: One way to tell if an international norm is robust is to assess the breadth of its support from a wide variety of important actors. We argue that, to assess norm robustness, we should look at the general beliefs, rhetorical support, and actions of both primary and secondary norm addressees (states and nonstate actors) at various levels: international, regional, domestic, and local. By way of example, we evaluate the robustness of international criminal law (ICL) norms by looking at the rhetoric and actions of a diverse set of international actors, including not only states and intergovernmental organizations but also ordinary publics, rebel groups, and nongovernmental organizations. Assessing evidence of norms beyond states leads us to conclude that the core ICL norms are robust, but their practical and institutional applicability are still contested. Contestation over applicability is important, and there are hints that it is growing, at least among some key actors, suggesting the possibility of ICL norm decay.